Kyrgyz Republic : Poverty Reduction Strategy Paper; Country Development Strategy (2007; 2010). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper analyzes progress on the Poverty Reduction Strategy Paper-Country Development Strategy (PRSP-CDS) in the Kyrgyz Republic for 2007-10. The CDS is the most important concept paper that outlines midterm vision of the Kyrgyz Republic. The paper also discusses that there is a clear need for development and implementation of the new effective strategy for country development with regard to the current situation that aims to overcome obstacles. Paradigm of the strategy implies the need to move toward employment of own resources and to focus on enhancement of competitiveness of the republic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet